Analysis of Rainwater Quality and Temperature Reduction Effects Using Rainwater Harvesting Facilities - JongSoo Choi; JungMin Lee; MyeongIn Kim; JaeHyeon Lee; YoungTae Cho (Buildings, 2024)
As eco-friendly complexes develop, interest in eco-friendly facilities is also growing. Particularly, rainwater harvesting facilities have demonstrated positive effects by reducing runoff to mitigate urban flooding and recycling water for landscaping and cleaning purposes. In this study, we analyzed the quality of stored rainwater, which has improved by excluding initial runoff, and examined the temperature reduction effects of road sprinkling and mist spraying. Road sprinkling decreased the temperature of asphalt and permeable pavements by approximately 15 °C, with permeable pavements maintaining the reduced temperature for a longer time. The indoor experiments with mist spraying showed a temperature reduction effect of 3.4 °C. The quality analysis of the rainwater harvesting facilities revealed that the water quality was suitable for irrigation and landscaping by excluding the initial runoff. This study confirms the effectiveness of rainwater utilization in mitigating urban heat islands and improving water circulation within cities.